PLANT SPECIES COMPOSITION OF THE FLOODPLAIN VEGETATION IN THE SONGKHLA LAKE BASIN - Anusit Cheechang; Kitichate Sridith (SEAMEO BIOTROP, 2026)
ARTICLE HIGLIGHTS- Floodplain vegetation in the Songkhla Lake Basin comprises 109 vascular plant species grouped into five community types.- Inundation depth and human disturbance are the main factors shaping plant community composition.- The flora is dominated by perennial terrestrial and helophytic (marsh) plants.- Human activities accelerate secondary succession in floodplain areas.- This process causes a decline of rare native species.- Urgent conservation measures are needed to protect native plants and maintain aquatic refugia.ABSTRACTThis study examined plant diversity in the threatened Songkhla Lake Basin floodplain, a vital yet degrading wetland. Carried out from September 2022 to January 2024 across ten plots using the Braun-Blanquet method and cluster analysis, the research aimed to document floristic composition, identify influencing factors, and assess the conservation status. As many as 109 vascular plant species (91 genera, 55 families) were identified in this study, mainly represented by Poaceae and Cyperaceae. Perennial terrestrial plants (64%) and helophytes (24.2%) were dominant. Five distinct vegetation communities were classified based on inundation depth. Results showed that human disturbances, such as agriculture and irrigation, speed up secondary succession, resulting in permanent habitat loss, decline of rare native species, and increased invasion by alien species. The findings emphasized an urgent need to conserve these remaining floodplain ecosystems.